2002
DOI: 10.1016/s0022-5347(05)64989-0
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Urological Laparoscopic Practices in the State of California

Abstract: Urological laparoscopic practice in California remains in its infancy. It is imperative that exposure should be increased in residency training programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 19 publications
0
10
0
1
Order By: Relevance
“…As supported by similar studies, the majority of laparoscopic urologic procedures were performed by younger surgeons and by surgeons who have been in practice for a short time. [6][7][8] Our study showed that urologists in academic hospitals, both in university hospitals and in education and research hospitals, tended to perform more laparoscopic surgeries. It appears that academic hospitals prioritize teaching the laparoscopic techniques that represent indispensable training for future urologists.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…As supported by similar studies, the majority of laparoscopic urologic procedures were performed by younger surgeons and by surgeons who have been in practice for a short time. [6][7][8] Our study showed that urologists in academic hospitals, both in university hospitals and in education and research hospitals, tended to perform more laparoscopic surgeries. It appears that academic hospitals prioritize teaching the laparoscopic techniques that represent indispensable training for future urologists.…”
Section: Discussionmentioning
confidence: 64%
“…In 2002, Kaynan et al [6] reported that only 12% of urologists successfully performed laparoscopy in California. Another study published in 2004 from the American Midwest revealed 21% of participants performed a significant amount of laparoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, a survey of urological laparoscopic practice patterns in the Midwest United States demonstrated that a total of 49% of urologists did not perform laparoscopy, 30% devoted less than 5% of their practice and 21% devoted 5% or more of their practice to laparoscopy (44). It is worth mentioning that in this series there were more urologists who spent at least 5% of their operative time on laparoscopy than in previous series in the United States (45)(46)(47).…”
Section: Where Do We Stand Now? -Future Aspectsmentioning
confidence: 59%
“…6,7 A recent survey of California surgeons demonstrated that 50% of urologists performing HALS were using it as a means of acquiring laparoscopic technique. 8 The tactile feedback offers the novice laparoscopist the familiarity of open surgery yet with the outcomes of minimally invasive surgery. Direct comparisons have been made with standard laparoscopic and open nephrectomy and nephroureterectomy, all demonstrating equivalent or better results and morbidity.…”
Section: Resultsmentioning
confidence: 99%